Financial Reporting Transparency as A Managerial Control Mechanism: A Case Study of Accounting Information System Implementation in An Environmental Consulting Firm - Dendra Aptanata Nugraha; Hujjatullah Fazlurrahman; Riska Dhenabayu; Muhammad Fajar Wahyudi Rahman (Jurnal Ekuilnomi, 2026)
This study examines changes in financial reporting transparency before and after the implementation of an Accounting Information System (AIS) and its implications for managerial control in a project-based environmental consulting firm. Using a qualitative comparative case study, data were collected through semi-structured interviews and analyzed thematically. Findings show that manual reporting created delays and limited monitoring, while AIS adoption improved integration, timeliness, and cost oversight. The findings contribute to the AIS literature by highlighting financial reporting transparency as an integral component of managerial control in project-based organizations